IgA-Based Solver for turbulence modelling on multipatch geometries. (November 2017) - Bastl, Bohumír; Brandner, Marek; Egermaier, Jiří; Michálková, Kristýna; Turnerová, Eva
Highlights: We present isogeometric analysis based solver for RANS equations with k-omega model for simulation of turbulent flows in 3D. Our solver can be used on multi-patch NURBS domains with non-conformal NURBS meshes, when discontinuous Galerkin approach is used to connect different NURBS patches into one computational domains. The results of our solver are compared to experimental results and to the results obtained from the standard CFD package. Abstract: This paper is focused on numerical solving of RANS (Reynolds-Averaged Navier-Stokes) equation with k − ω model for simulation of turbulent flows in 3D. The solver which is based on a recently proposed approach called isogeometric analysis is presented. This numerical method is based on isoparametric approach, i.e., the same basis functions are used for the description of a geometry of a computational domain and also for the representation of a solution. As computational domains are described by NURBS objects in isogeometric analysis, any real application requires to handle the so-called multipatch domains, where the computational domain is composed of more parts and each part is represented by one NURBS object. In our solver, discontinuous Galerkin method is used to connect different NURBS patches into one computational domain. The results of the solver are demonstrated on a standard benchmark example – backward facing step.